EFFECT PROPAGATION IN A TOXICOKINETIC/TOXICODYNAMIC MODEL EXPLAINS DELAYED EFFECTS ON THE GROWTH OF UNICELLULAR GREEN ALGAE SCENEDESMUS VACUOLATUS. (2nd April 2013) - Vogs, Carolina; Bandow, Nicole; Altenburger, Rolf
Abstract: Ecotoxicological standard tests assess toxic effects by exposing an organism to high concentrations over defined periods of time. To evaluate toxicity under field conditions such as fluctuating and pulsed exposures, process‐based toxicokinetic/toxicodynamic (TK/TD) models may be used for extrapolation from the existing evidence. A TK/TD model was developed that simulates the effect on growth of the green algae Scenedesmus vacuolatus continuously exposed to the model chemicals norflurazon, triclosan, and N ‐phenyl‐2‐naphthylamine. A pharmacological time–response model describing the effects of anticancer treatments on cancer cell growth was adapted and modified to model the affected growth of synchronized algae cells. The TK/TD model simulates the temporal effect course by linking the ambient concentration of a chemical to the observable adverse effect via an internal concentration and a sequence of biological events in the organism. The parameters of the toxicodynamic model are related to the growth characteristics of algae cells, a no effect concentration, the chemical efficacy as well as the ability of recovery and repair, and the delay during damage propagation. The TK/TD model fits well to the observed algae growth. The effect propagation through cumulative cell damage explained the observed delayed responses better than just the toxicokinetics. The TK/TD model could facilitate the link between several effect levels within damage propagation, which prospectively may be helpful to model adverse outcome pathways and time‐dependent mixture effects. Environ. Toxicol. Chem. 2013;32:1161–1172. © 2013 SETAC